2013
DOI: 10.1186/1477-9560-11-18
|View full text |Cite
|
Sign up to set email alerts
|

The new oral anti-coagulants and the phase 3 clinical trials - a systematic review of the literature

Abstract: BackgroundAnticoagulation with vitamin K antagonists such as warfarin has historically been used for the long term management of patients with thromboembolic disease. However, these agents have a slow onset of action which requires bridging therapy with heparin and its analogues, which are available only in parenteral route. To overcome these limitations, new oral anticoagulants such as factor Xa inhibitors and direct thrombin inhibitors have been developed. The aim of this article is to systematically review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…After feasibility studies [5,6], EINSTEIN clinical trials were initiated to test the efficacy of rivaroxaban as a single agent for the management of symptomatic VTE. The results of the EINSTEIN-DVT [7] and EINSTEIN-PE [8] studies demonstrated non-inferiority of rivaroxaban (15 mg twice daily for 3 weeks, followed by 20 mg once daily) versus standard classical treatment (heparin and VKAs) in terms of the primary outcome (recurrent VTE) (2.1% in the rivaroxaban group vs. 3% in the control group; P b 0.001) [9].…”
Section: Introductionmentioning
confidence: 99%
“…After feasibility studies [5,6], EINSTEIN clinical trials were initiated to test the efficacy of rivaroxaban as a single agent for the management of symptomatic VTE. The results of the EINSTEIN-DVT [7] and EINSTEIN-PE [8] studies demonstrated non-inferiority of rivaroxaban (15 mg twice daily for 3 weeks, followed by 20 mg once daily) versus standard classical treatment (heparin and VKAs) in terms of the primary outcome (recurrent VTE) (2.1% in the rivaroxaban group vs. 3% in the control group; P b 0.001) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Non-vitamin K antagonist oral anticoagulants (NOACs) such as dabigatran were developed to overcome the major drawbacks of vitamin K antagonists (VKAs), in particular their need for continuous effect monitoring [4]. Dabigatran etexilate is rapidly hydrolyzed to its active form dabigatran after oral administration and intestinal absorption by non-specific ubiquitous esterases in gut, blood, and liver [5,6]. Peak plasma concentration are attained 2 h after ingestion [7], and the terminal half-life time was determined to be 12-17 h in patients with normal creatinine clearance [5], allowing for a fixed daily dosing regimen without the need to routinely monitor coagulation for dose adjustment [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 3 years, following successful phase 3 clinical trials, three agents(dabigatran, apixaban and rivaroxaban) have been incorporated into guidelines worldwide and more NOACs are in the pipeline [38][39][40] . As with statins, ACEIs, ARBs and other CVD drug classes, "me-too" agents are anticipated and trials are already underway [41][42][43][44] . "Me-too" drugs are expensive and do not serve society well [41][42][43] .…”
Section: New Drugs and New Trialsmentioning
confidence: 99%
“…Based on trials or predicted trial outcomes (for edoxaban 44 NOACs, like warfarin, and all drugs, have risks(excess bleeding) as well as benefits (prevention of stroke/thromboembolism). Trial data may be used to estimate risks as well as benefits, and to compare different agents.…”
Section: New Drugs and New Trialsmentioning
confidence: 99%